Media Edpuzzle dalam Pembelajaran Menyimak Bahasa Jerman - Jusnidar Jusnidar; Misnah Mannahali; Abdul Kasim Achmad (Universitas Negeri Makassar, 2022)
Abstract. The purpose of this study was to determine and describe the effectiveness of using Edpuzzle media on the learning outcomes of listening to German students in class XI MIPA SMAN 8 Makassar. This type of research is a quasi-experimental design (non-equivalent control group design). The population of this research is the students of class XI MIPA SMAN 8 Makassar. The subjects of this study were students of class XI MIPA 3 as the experimental class and students of class XI MIPA 4 as the control class which were selected randomly (random sampling). The instrument in this study was a test consisting of multiple choice and true-false tests. Data analysis using the Independent sample t-test test shows the value of > that is 2.610 > 2.00665 and the value of Asymp. Sig. (2-tailed) of 0.012 (p<0.05)). That is, the results of this study indicate that the use of Edpuzzle is effective on the learning outcomes of listening to German for students in class XI SMAN 8 Makassar.